An Analysis Study Flood Improving The Capacity Reduction Long Storage And Bozem: ( A Case Study In One Of The Factories A Coffee At Sidoarjo Regency) - Irfan Nur Rozzaq; Diah Ayu Restuti Wulandari (Journal of World Conference (JWC), 2020)
. Industry is an important infrastructure in the city. At the location of the coffee factory in the village of Bringinbendo, Sidoarjo with an area of ??± 119,372 m², there is a lack of green open space and small dimensions so that it cannot accommodate the water discharge during high rainfall. The analysis data used is 10 years of rainfall data observations from the data Rain Station of Botokan, Sruni, Ketegan and Karangnongko. In this study the method used Log Pearson Type III method. So that the 5 year return rain discharge is 105.75 m³/sec. The existing channel capacity is 4040.42 m³ while the required volume is 4947.16 m³ with a flood discharge of 2,450 m³ / sec. Then it needs a long storage with a capacity of 2575 m³ and bozem with a capacity of 337.5 m³ so that it can accommodate the volume of water.